Pengembangan Digital Book Berbasis PBL untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV SD Negeri Ponowareng 01 - Muhammad Arief Rohman; M. Arief Rohman; Ida Dwijayanti; Sumarno (STKIP Subang, 2026)
ABSTRACT The problems in this research are (1) What is the validity of the PBL-based Digital Book developed to improve the critical thinking skills of fourth grade students at SDN Ponowareng 01?, (2) What is the practicality of the PBL-based Digital Book developed to improve critical thinking skills for fourth grade students at SDN Ponowareng 01? (3) What is the effectiveness of the PBL-based Digital Book that was developed to improve the critical thinking skills of grade IV students at SDN Ponowareng 01? The aims of this study were (1) to develop and produce a valid PBL-based digital book to improve the critical thinking skills of fourth grade students at SDN Ponowareng 01, (2) to develop and produce a practical PBL- based digital book to improve critical thinking skills for fourth grade students at SDN Ponowareng 01, (3) Develop and produce an effective PBL-based Digital Book to improve the critical thinking skills of grade IV students at SDN Ponowareng 01. The subjects in this study were grade IV students at SDN Ponowareng 01 and SDN Smbangdesa, totaling 80 students. Data collection methods used are questionnaires, documentation and tests to students at the beginning and end of learning. Data analysis used is descriptive analysis, pre- requisite test, and hypothesis testing. From the results of the study it can be seen that the validation results from the validators show that the PBL-based digital book to improve the critical thinking skills of grade IV students at SDN Ponowareng 01 which has been developed is valid and feasible to use. The results of the study show that the percentage of product achievement from media experts is 83%, this figure is in good qualification and is said to be valid and does not need revision. The percentage of product achievement from material experts is 83.84% valid and does not need revision. PBL-based digital book to improve critical thinking skills of grade IV students at SDN Ponowareng 01 which was developed to be practical to use. From the results of teacher and student responses to PBL-based digital book learning media on style material in everyday life, it can be concluded that they have a very positive response. The PBL-based digital book to improve the critical thinking skills of grade IV students at SDN Ponowareng 01 which has been developed is less effective. The results of the data analysis show that 91.67% of students complete. The highest student score was 100, the lowest student score was 64, the average student score was 82.94, the number of students who completed 33 students out of 36 students and 3 students did not complete. The results of data analysis of the N-Gain index are 44.89%, this indicates that the products used to improve critical thinking skills are less effective.